PENGARUHÃÂ PRESTASIÃÂ BELAJARÃÂ DANÃÂ PRESTASIÃÂ PRAKTIKÃÂ PENGALAMANÃÂ LAPANGANÃÂ TERHADAPÃÂ MINATÃÂ MAHASISWAÃÂ MENJADIÃÂ GURUÃÂ ÃÂ - Yulirtanto, BibitÃƒÂ‚Ã‚Â ; ÃƒÂ‚Ã‚Â BurhanÃƒÂ‚Ã‚Â , M.; Hadromi, - (Jurnal Pendidikan Teknik Mesin, 2008)
TujuanÃÂ penelitianÃÂ iniÃÂ adalahÃÂ mengetahui:ÃÂ (1)ÃÂ prestasiÃÂ belajar,ÃÂ prestasiÃÂ PPLÃÂ danÃÂ minatÃÂ mahasiswaÃÂ menjadiÃÂ guru;ÃÂ  (2)ÃÂ  PengaruhÃÂ  prestasiÃÂ  belajarÃÂ  danÃÂ  PPLÃÂ  terhadapÃÂ  minatÃÂ  mahasiswaÃÂ  menjadiÃÂ  guru;ÃÂ  (3)ÃÂ  PengaruhÃÂ  prestasiÃÂ belajarÃÂ  terhadapÃÂ  minatÃÂ  mahasiswaÃÂ  menjadiÃÂ  guru;ÃÂ  danÃÂ  (4)ÃÂ  PengaruhÃÂ  prestasiÃÂ  PPLÃÂ  terhadapÃÂ  minatÃÂ  mahasiswaÃÂ menjadiÃÂ  guruÃÂ  SMK.ÃÂ PopulasiÃÂ  penelitianÃÂ  adalahÃÂ 80ÃÂ  orangÃÂ mahasiswaÃÂ PTMÃÂ 2005ÃÂ denganÃÂ  jumlahÃÂ  sampelÃÂ  45ÃÂ orang.ÃÂ PengambilanÃÂ  sampelÃÂ  menggunakanÃÂ  teknikÃÂ  randomÃÂ  sampling.ÃÂ  TeknikÃÂ  pengumpulanÃÂ  dataÃÂ  menggunakanÃÂ dokumentasi,ÃÂ observasiÃÂ danÃÂ angket.ÃÂ TeknikÃÂ analisisÃÂ yangÃÂ digunakanÃÂ  adalahÃÂ deskriptif,ÃÂ  regresiÃÂ gandaÃÂ danÃÂ parsial.ÃÂ AnalisisÃÂ  deskriptifÃÂ menunjukkanÃÂ  bahwaÃÂ  prestasiÃÂ  belajar,ÃÂ  prestasiÃÂ  PPLÃÂ  danÃÂ minatÃÂ menjadiÃÂ  guruÃÂ  SMKÃÂ mahasiswaÃÂ PendidikanÃÂ  TeknikÃÂ MesinÃÂ  UnnesÃÂ  berturutÃ¢â¬ÂturutÃÂ memenuhiÃÂ  kriteriaÃÂ  sangatÃÂ memuaskan,ÃÂ  sangatÃÂ  tinggiÃÂ  danÃÂ  tinggi.ÃÂ AnalisisÃÂ  regresiÃÂ  gandaÃÂ menunjukkanÃÂ  pengaruhÃÂ  prestasiÃÂ  belajarÃÂ  danÃÂ  prestasiÃÂ  PPLÃÂ  terhadapÃÂ minatÃÂ menjadiÃÂ  guruÃÂ sebesarÃÂ 79,60%. ÃÂ  KataÃÂ Kunci:ÃÂ PraktikÃÂ PengalamanÃÂ LapanganÃÂ (PPL),ÃÂ MinatÃÂ MenjadiÃÂ GuruÃÂ SMKÃÂ TheÃÂ aimsÃÂ ofÃÂ thisÃÂ researchÃÂ areÃÂ toÃÂ discover:ÃÂ (1)ÃÂ theÃÂ studyÃÂ achievement,ÃÂ fieldÃÂ experienceÃÂ practice,ÃÂ andÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ toÃÂ beÃÂ teachers;ÃÂ (2)ÃÂ theÃÂ effectÃÂ ofÃÂ studyÃÂ achievementÃÂ andÃÂ fieldÃÂ experienceÃÂ practiceÃÂ towardÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ toÃÂ beÃÂ teachers;ÃÂ (3)ÃÂ theÃÂ effectÃÂ ofÃÂ studyÃÂ achievementÃÂ towardÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ toÃÂ beÃÂ teachers;ÃÂ (4)ÃÂ theÃÂ effectÃÂ ofÃÂ fieldÃÂ experienceÃÂ practiceÃÂ towardÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ toÃÂ beÃÂ vocationalÃÂ highÃÂ schoolÃÂ teachers.ÃÂ TheÃÂ populationÃÂ ofÃÂ thisÃÂ researchÃÂ wasÃÂ 80ÃÂ studentsÃÂ ofÃÂ MechanicalÃÂ EngineeringÃÂ EducationÃÂ yearÃÂ 2005ÃÂ withÃÂ 45ÃÂ studentsÃÂ asÃÂ sample.ÃÂ TheÃÂ sampleÃÂ takingÃÂ usedÃÂ randomÃÂ samplingÃÂ technique.ÃÂ TheÃÂ dataÃÂ collectedÃÂ usedÃÂ documentation,ÃÂ observation,ÃÂ andÃÂ questionnaire.ÃÂ TheÃÂ  analysisÃÂ  techniquesÃÂ  usedÃÂ  wereÃÂ  descriptive,ÃÂ  doubleÃÂ  regression,ÃÂ  andÃÂ  partialÃÂ  technique.ÃÂ  DescriptiveÃÂ  analysisÃÂ showsÃÂ thatÃÂ theÃÂ studyÃÂ achievement,ÃÂ fieldÃÂ experienceÃÂ practice,ÃÂ andÃÂ MechanicalÃÂ EngineeringÃÂ EducationÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ toÃÂ beÃÂ vocationalÃÂ highÃÂ schoolÃÂ teachersÃÂ successfullyÃÂ fulfillÃÂ  veryÃÂ  satisfactoryÃÂ  criteria,ÃÂ  veryÃÂ  high,ÃÂ  andÃÂ  high.ÃÂ DoubleÃÂ regressionÃÂ analysisÃÂ showsÃÂ theÃÂ percentageÃÂ ofÃÂ theÃÂ effectÃÂ ofÃÂ studyÃÂ achievementÃÂ andÃÂ fieldÃÂ xperienceÃÂ practiceÃÂ achievementÃÂ towardÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ toÃÂ beÃÂ teachersÃÂ isÃÂ 79,60%. ÃÂ  Keywords:ÃÂ FieldÃÂ ExperienceÃÂ PracticeÃÂ (ppl),ÃÂ interestÃÂ toÃÂ beÃÂ vocationalÃÂ highÃÂ schoolÃÂ teachers ÃÂ